Nucleation mechanism of electrochemical deposition of Cu on reduced graphene oxide electrodes - Yan, Qingyu (2013)
The nucleation mechanism of electrochemical deposition of Cu on reduced graphene oxide (rGO) electrodes has been systematically studied on the basis of the cyclic voltammetry, Tafel plot, and chronoamperometry. Our results show that the experimental parameters including electrolyte concentration, deposition potential, solution pH, and the presence of background electrolyte can determine the nucleation mechanism. Scanning electron microscopy is employed to study the nucleation and growth of Cu on rGO electrodes. This study is significant in development of the electrochemical method in practical applications based on the rGO electrodes.